Construction of Key Echange Protocol over Max-Plus Algebra to Encrypt and Decrypt Arabic Documents - Any Muanalifah (Journal of Natural Sciences and Mathematics Research, 2015)
In this paper, we consider the operation of matrix in Max-plus Algebra to construct a key public to encrypt and decrypt arabic document. Matrix operation in max-plus algebra is slight different with matrix operation in classical. In this paper, we also use a modular 37 to translate it into arabic text (arabic letter with number and special character).